Anisotropic model observing pulsars from Neutron Star Interior Composition with modified Van der Waals equation of state - S. A. Mardan; A. Khalid; Rubab Manzoor; Muhammad Bilal Riaz (European Physical Journal C: Particles and Fields)
Abstract This paper is designed for heavy pulsars coming from the Neutron Star Interior Composition Explorer. The research model is describe by Einstein field equations for anisotropic fluid configuration with spherical symmetry. As per present perceptiveness, modified non-linear Van der Waals equation of state is used to relate physical variables. The continuity of inner and outer matter is obtained by comparing inner spacetime to outer Schwarzschild metric. The physical viability of this model is evaluated and further it is compared with observational data of pulsars PSR J0348+0432, PSR J0740+6620 and PSR J0030+0451. The model fulfils all physical and mathematical characteristics of the dense structure studies. It offers the factual proofs carried by evolution of celestial configurations. The working model presented here is physically viable and shows stable behaviour.